Designing Web-Based Recruitment System With Applicant Tracking System Feature at PT Reza Karya Abadi - Gunawan, Faiz -; Karnowahadi, Karnowahadi -; Suwardi, Suwardi - (Admisi dan Bisnis, 2023)
PT Reza Karya Abadi is an outsourcing company that was founded in 2009. As an outsourcing company, core business of PT Reza Karya Abadi is to provide manpowers to clients. At this time, the recruitment system at PT Reza Karya Abadi is still using the traditional way. Therefore, the recruitment process at PT Reza Karya Abadi takes a lot of time and effort and there is frequently a mismatch between the candidates provided and client needs. Creating a recruitment system with web-based ATS features can be a solution for companies to find suitable candidates and make the recruitment process more efficient. The process of developing a web-based recruitment system is carried out using the waterfall method. The implementation of this system is limited to the process of managing vacancies, managing candidates and implementing ATS features for the admin side, while from the applicant's side the implementation is limited to the process of managing personal data, submitting applications and applicant status. Testing of this system using the blackbox method. The results of this study are in the form of a web recruitment system for PT Reza Karya Abadi which can make it easier for applicants to submit applications and make it easier for admins to find suitable candidates